Thermal shock fracture analysis of auxetic honeycomb layer based on non-Fourier heat conduction. (15th March 2023) - Hu, J.S.; Wang, B.L.; Hirakata, H.; Wang, K.F.
Highlights: The non-Fourier thermal fracture of an auxetic honeycomb layer investigated theoretically. The temperature field will be unaffected by non-Fourier effects if t / τ * > 12.2. The non-Fourier effect reduces the thermal shock resistance by 34%. The auxetic property can enhance the thermal shock resistance. Abstract: Auxetic honeycomb layer (HL) is a typical metamaterial with a negative Poisson's ratio. In this paper, the thermal shock fracture problem of the auxetic HL is investigated based on non-Fourier heat conduction. The uncracked non-Fourier temperature and thermal stress field are determined by the separation of variables method and the constitutive model of auxetic HL. The corresponding thermal stress intensity factor (TSIF) is obtained in numerical form. Based on the TSIF and the fracture toughness criterion, the critical temperature of auxetic HL is predicted. There is a clear difference between the results based on the non-Fourier and Fourier models. The maximum thermal stress and TSIF of the auxetic HL obtained from the non-Fourier model are both significantly higher than those obtained from the Fourier model. If non-Fourier effects are not taken into account, the critical temperature of the auxetic HL is also overestimated. In addition, the auxetic property can increase the critical temperature of the HL, whether based on the non-Fourier or Fourier model. The results demonstrate the good potential of the auxetic HL in the thermal protection system application.